The Ma’atenu communication rituals of Pelauw Muslims community - Sulaeman Sulaeman; Kamaruzzaman Kamaruzzaman; Mahdi Malawat (Faculty of Social and Political Science, Universitas Airlangga, 2019)
The purpose of this research is to analyse of the symbols Ma’atenu ritual communication process of Pelauw Muslims community. Ma’atenu is an integral part of rituals society, held as the fusion of Islamic teachings interaction with the values of local wisdom. The rituals started with prayer using various media such as machetes, swords, tifa, tambourine, and immune test to from as power of ancestral spirits by cutting, slicing and stabbing body parts such as stomach, chest, hands, feet, neck, cheeks, tongue, and head. This research employed a subjective interpretive paradigm with ethnography communication approach by Dell Hymes based on symbolic interaction perspective. Involving 17 informants with one ma’ahala lahat, one ma’ataru ame, three kings of the country, three mothers and/or wives, and the remaining nine practitioners of ritual communication actions from the western, southern and eastern sectors chose purposively. The study finds that Ma’atenu communication event act as symbols of the ritual home clan (small clan, parent clan, and merger clan), the sacred meal, self-cleaning action ritual communication action, self-cleaning action, and fabric wreath. Any communication event represents symbols of devotion, struggle, disposal of a bad attitude, immunity and power, and self-recovery. Communication consists of pattern between communication components that forms pattern within Ma’atenu rituals appear in plea to God, veneration of ancestral spirits, and social solidarity of Muslims in Pelauw.